Et’hem Beu mosque, Tirana, a sparkle of Islamic architecture in Albania - Soomro, Ali Raza; Basha, Brunilda (Sci.Int.(Lahore), 2014)
During the centralization of the Turkish Empire had reached its peak in fifteen and sixteen (XV-XVI) centuries, Ottoman art in Albania was very similar of that in Skopje or Edirne. On the other hand in the seventeenth (XVII) centu- ry, when the influence of the central Ottoman government slowly declined; the local contribution to Islamic buildings in Albania gradually increased. In the late eighteenth century and early nineteenth (XVIII-XIX) century, the blending of Ottoman elements reached its peak with the appearance of a particular style of Albanian-Islamic Architecture. This style presents a synthesis of religious and secular elements such as ottoman, local and western. The fusion of these features seemingly heterogeneous reflects indeed the country of Albania in history, as a con- necting route of the East and West. These recent works, as named by Machiel Kiel, (2011) [16] are the products of the "Golden century of Islamic culture in Albania". This time is considered as the "golden age" in terms of architectural development in Albania. This paper attempts to unfold how Islam was spread in region of Albania and how the religious buildings adapted the Islamic elements breathing harmoniously with the local architectural elements. In this regard the case study of Et’hem Beu Mosque of Tirana has been conducted to unfold the facts of a relationship of local Islamic features and European architecture through literature review on Islam in Albania, detailed description on Mosque background, his- tory and its architectural implication has been presented. Eventually this study will promote the evolution of Islamic architecture in Albania and its significance in Albanian architectural development.